2017
DOI: 10.1002/pi.5322
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molar mass on the thermal properties, conductivity and intermolecular interaction of poly(ethylene oxide) solid polymer electrolytes

Abstract: The sample preparation pathway of solid polymer electrolytes (SPEs) influences their thermal properties, which in turn governs the ionic conductivity of the materials especially for systems consisting of a crystallizable constituent. Majority of poly(ethylene oxide) (PEO)‐based SPEs with molar masses of PEO well above 104 g mol−1 (where PEO is crystallizable and should reach an asymptote in thermal behaviour) display molar mass dependence of the thermal properties and ionic conductivities in non‐equilibrium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…PEO 1 at Y S = 0.15) in reducing the melting temperature of PEO to around 60 °C or below (data after Ref. ), the sample moves towards liquid‐like behavior.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…PEO 1 at Y S = 0.15) in reducing the melting temperature of PEO to around 60 °C or below (data after Ref. ), the sample moves towards liquid‐like behavior.…”
Section: Resultsmentioning
confidence: 95%
“…Δ C p is a measure of mass fraction of the amorphous microphase in the two‐phase system (crystalline PEO and amorphous mixture of PEO + Li). Below the solubility limit of PEO, Δ C p increases linearly with W S . Since the change in heat capacity can also be correlated to the measure of non‐crystalline material, it can be concluded that at M ɳ = const , Δ C p increases with ascending salt concentration due to the increasing amount of amorphous phase.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations